2008
DOI: 10.1007/s11064-008-9880-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Gi Proteins Participate in Nerve Growth Factor-Induced Activation of c-Jun N-terminal Kinases in PC12 Cells

Abstract: Nerve growth factor (NGF)-mediated activation of mitogen-activated protein kinases (MAPK) is critical for differentiation and apoptosis of PC12 cells. Since NGF employs stress-activated c-Jun N-terminal kinase (JNK) to regulate both programmed cell death and neurite outgrowth of PC12 cells, we examined NGF-regulated JNK activity and the role of G(i/o) proteins. Induction of JNK phosphorylation by NGF occurred in a time- and dose-dependent manner and was partially inhibited by pertussis toxin (PTX). To discern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 75 publications
3
9
0
Order By: Relevance
“…Without the inhibitor, NGF-induced neurite outgrowth was clearly visible at both 6 and 24 h after stimulation. When NGF was not replenished, neurites were largely degenerated after 48 h. Pretreatment of cells with SP600125 decreased NGF-induced neurite outgrowth by ϳ60% at 6 h and 24 h. This result is in line with previous studies showing that JNK is an important mediator for neuronal differentiation in PC12 cells (23,26,39,40). To analyze JNK activity, we quantified phosphorylation levels via Western blotting (Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Without the inhibitor, NGF-induced neurite outgrowth was clearly visible at both 6 and 24 h after stimulation. When NGF was not replenished, neurites were largely degenerated after 48 h. Pretreatment of cells with SP600125 decreased NGF-induced neurite outgrowth by ϳ60% at 6 h and 24 h. This result is in line with previous studies showing that JNK is an important mediator for neuronal differentiation in PC12 cells (23,26,39,40). To analyze JNK activity, we quantified phosphorylation levels via Western blotting (Fig.…”
Section: Resultssupporting
confidence: 89%
“…These proteins showed increased levels 0.5 h to 2 h after NGF treatment followed by a steady decrease over time below control levels at 24 h. This finding suggests that NGF-dependent JNK activation might be induced via multiple G-proteins. Indeed, it has been shown that several G-proteins are involved in JNK activation during PC12 cell differentiation (25,26) and that Rap1 is involved in NGF-induced PC12 cell differentiation (44,45).…”
Section: Jnk Interacts With Proteins Of Different Molecular Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the findings that demonstrate the localization of GPCRs and their signaling components in lipid rafts and caveolae [63], dimerization of GPCRs [64], and trans-activation of receptor tyrosine kinases by GPCRs [65]. In the case of cell differentiation, examples of novel GPCR signaling mechanism include transactivation of TrkA by purinergic P2Y2 receptor [12], and mediation of partial NGF signaling by G i/o proteins [14,17,18]. With new discoveries in the signaling mechanisms of GPCRs and novel ligands for orphan receptors, we will undoubtedly appreciate the significance of G protein-linked signaling in the differentiation of various cell lineages and development of tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of PI3K/Akt pathway by NGF is in part mediated through the Gβγ subunit released from activated G i/o , which promotes the phosphorylation of translation regulator tuberlin to enhance neuronal survival [14,15]. In a similar manner, G i/o mediates part of the NGF-induced p38 and JNK phosphorylations, which are required for neuronal differentiation [17,18]. These examples suggest bidirectional crosstalk between GPCR and NGF signaling in the regulation of neuronal survival and differentiation.…”
Section: The Functions Of G Protein Signaling In Neuronal Differentiamentioning
confidence: 99%